The Sopranos : the complete third season - Chase, David; Coulter, Allen; Gandolfini, James; Bracco, Lorraine, 1955-; Falco, Edie; Brad Grey Television; HBO Original Programming; HBO Video (Firm) (New York : HBO Home Video, 2002)
Complete third season of the television program The Sopranos.
Mr. Ruggiero's neighborhood / written by David Chase; directed by Allen Coulter -- Proshai, Livushka / written by David Chase; directed by Tim Van Patten -- Fortunate son / written by Todd A. Kessler; directed by Henry J. Bronchstein -- Employee of the month / written by Robin Green, Mitchell Burgess; directed by John Patterson -- Another toothpick / written by Terence Winter; directed by Jack Bender -- University / written by Terence Winter, Salvatore J. Satbile; directed by Allen Coulter -- Second opinion / written by Lawrence Konner; directed by Tim Van Patten -- He is risen / written by Robin Green, Mitchell Burgess; directed by Allen Koulter -- The telltale moozadell / written by Michael Imperioli; directed by Daniel Attias -- To save us all from Satan's power / written by Robin Green, Mitchell Burgess; directed by Jack Bender -- Pine barrens / written by Terence Winter; directed by Steve Buscemi -- Amour fou / written by Frank Renzulli; directed by Tim Van Patten -- The army of one / written by David Chase, Lawrence Konner; directed by John Patterson.
Features: Audio commentary with Michael Imperioli, Steve Buscemi, David Chase, theatrical trailers, behind-the-scenes featurettes, episodic recaps and scene selections.
James Gandolfini, Lorraine Bracco, Edie Falco, Michael Imperioli, Dominic Chianese.
Not rated.
DVDs, Dolby digital surround.
In English, French or Spanish.
Closed-captioned.
Keywords: Organized crime -- Drama; Mafia -- Drama; Television programs; Video recordings for hard of hearing people